Isothermal Kinetics of Catalyzed Air Oxidation of Diesel Soot - Ram Prasad; Venkateswara Rao Bella (Bulletin of Chemical Reaction Engineering & Catalysis, 2010)
To comply with the stringent emission regulations on soot, diesel vehicles manufacturers more and more commonly use diesel particulate filters (DPF). These systems need to be regenerated periodically by burning soot that has been accumulated during the loading of the DPF. Design of the DPF requires rate of soot oxidation. This paper describes the kinetics of catalytic oxidation of diesel soot with air under isothermal conditions. Kinetics data were collected in a specially designed mini-semi-batch reactor. Under the high air flow rate assuming pseudo first order reaction the activation energy of soot oxidation was found to be, Ea = 160 kJ/ mol. © 2010 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)